Implementasi Akuntabilitas Dalam Konsep Metafora Amanah di Lembaga Bisnis Syariah (Studi Kasus : Swalayan Pamella Yogyakarta) - Kalbarini, Rahmah Yulisa; Suprayogi, Noven (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This study is aimed to find out accountability within Trustful metaphor concept andÂ know the process also type of accountability in islamic business organization case study atÂ Pamella Supermarket.The methods of this study is qualitative approach using research study. The analyzeÂ technique is domain and taxonomy. Data is collected by interview, passive participantÂ observation, and secondary data. The informants of this research are an assistant manager,Â a marketing officer, an employee and costumers of the Pamella Swalayan in Yogyakarta.The results obtained, that the implementation of accountability with trustful metaphorÂ concept in Pamella Supermarket based on pamella ownerâs concept on accountability thatÂ the purpose of life is rahmatan lil alamin that is each muslim can give a benefit to of theÂ muslims. The realization of that concept is there will be a separation of responsibility :Â business fund from social fund which is managed by Pamella. From the supermarket sight,Â the business fund is under the responsibility of the owner and to Allah SWT. While the socialÂ fund is under the responsibility of the society by holding some social humanity program,Â which are reported to the society as well as to the existing interrelated departments inÂ Yogyakarta.